Long-duration Parkinson's disease: Role of lateralization of motor features - Munhoz, Renato P.; Espay, Alberto J.; Morgante, Francesca; Li, Jie-Yuan; Teive, Helio A.; Dunn, Emily; Gallin, Eliza; Litvan, Irene (Parkinsonism & related disorders, 2013)
A mean of 10 years elapse before patients with Parkinson's disease (PD) reach Hoehn & Yahr (H&Y) stage 4, and 14 years for stage 5. A small proportion of PD patients survive and are ambulatory for ≥20 years. We sought to identify features associated with long-duration PD (dPD). This five-center, case–control study compared 136 PD patients with ≥20 years of duration and H&Y stage ≤4 (dPD) to 134 H&Y-, age- and gender-matched PD patients between 10 and 15 years of disease (cPD). By study design, there were no between-group differences in age, gender and H&Y. dPD subjects were younger at onset (p < 0.0001), had more psychosis (p: 0.038), were receiving higher levodopa equivalent daily doses (p: 0.02), were predominantly left-handed (p: 0.048), and had greater frequency of left-sided onset (p: 0.015) compared to cPD subjects. Both groups had similar rates of resting tremor, dementia and REM sleep behavior disorder. Early disease onset, left-handedness and left-sided onset are associated with long disease and ambulatory PD survival. The neurobiological basis of the prognostic value of lateralization deserves further investigation.